Hubungan Burnout dengan Mekanisme Koping pada Perawat Pelaksana di Ruang Rawat Inap Rumah Sakit Jiwa Daerah Provinsi Jambi - Qadriannis Fitri; Mila Triana Sari; Dwi Yunita Rahmadhani (Universitas Baiturrahim, 2022)
Nurses who work in hospitals are at high risk of experiencing burnout. A person who experiences burnout will lose the meaning of his job because of a prolonged response to emotional, physical, and mental exhaustion experienced. Burnout is physical, emotional, and mental exhaustion due to being in an emotionally demanding situation. Factors that cause nurses to experience burnout are patient demands, possible dangers in providing nursing care, heavy workloads or pressure when they have to provide a lot of care for many patients during work shifts. The purpose of this study was to determine the relationship between burnout and coping mechanisms for nurses in the inpatient ward of the Jambi Provincial Mental Hospital. This research is a quantitative research using cross sectional method. The sampling technique used is total sampling with a sample of 86 people, the research instrument using a questionnaire was analyzed univariately and bivariately using the chi-square test. The results showed that 55.8% of nurses experienced burnout and 60.5% of nurses had adaptive coping mechanisms. The results of the chi-square statistical test obtained p-value = 0.000. Which means that there is a significant relationship between burnout and coping mechanisms for nurses in the inpatient room of the Jambi Provincial Mental Hospital. It is hoped that they can apply more persuasive management by conducting communication forums to discuss problems at work and provide guidance in order to improve the performance of nurses.